2022
DOI: 10.1186/s40814-022-01051-x
|View full text |Cite
|
Sign up to set email alerts
|

Protocol for SonoSpeech Cleft Pilot: a mixed-methods pilot randomized control trial of ultrasound visual biofeedback versus standard intervention for children with cleft lip and palate

Abstract: Background Children with cleft lip and palate can continue to have problems producing clear speech after surgery. This can lead to social, emotional, and educational challenges. Typical treatment involves teaching children the correct tongue movements to produce speech sounds. This is known as articulation intervention. However, this intervention is challenging because the tongue is hidden from view and movements are difficult to see and describe. This pilot randomized control trial will try a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…This study reported on the acceptability of UVBF versus standard treatment as part of a pilot feasibility trial (Cleland et al, 2022). Results met our objectives: in both intervention arms more than 75% of families rated randomization as acceptable in a questionnaire.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…This study reported on the acceptability of UVBF versus standard treatment as part of a pilot feasibility trial (Cleland et al, 2022). Results met our objectives: in both intervention arms more than 75% of families rated randomization as acceptable in a questionnaire.…”
Section: Discussionmentioning
confidence: 88%
“…This study was approved by the West Midlands -South Birmingham Research Ethics Committee (21/WM/0104). The trial was registered on the 22nd of March, 2021 ISRCTN17441953 and the protocol was published prior to data collection (Cleland et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations